Comparison of Heavy Metals (Pb, Cd, Zn) Concentrations in the Industrial, Agricultural Areas and Highway Soils of Amol and Babol Towns (Mazandaran, Iran 2008) - Amouei AI, Mahvi AH , Naddafi K (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Considering the existence of valuable natural resources such as forest, river, sea and agricultural areas in Mazandaran province on the one hand and development of industrial and agricultural centers on the other hand, supervision and control of environmental health condition is necessary. This study was done to evaluate Pb, Cd and Zn concentrations in the industrial, agricultural areas and highway soils of Amol and Babol towns, Iran.METHODS: In this cross sectional study, 192 soil samples based on easy sampling were collected from studied areas. These samples were dried in oven and grounded and then passed through polyethylene sieve with 2mm holes. PH, Organic Carbon, Cation exchange capacity and texture of soils were determined based on ASTM (American Standards for Testing of Materials (ASTM). Extraction of samples was performed by HNO3 and HCL. Zn, Cd and Pb (mg/Kg) in soil were determined by Atomic Absorption Spectrophotometer Perkin-Elmer 603. FINDINGS: Mean concentration of Pb in the industrial, agricultural and highway soils was 213±132, 19.7±9.5 and 84±38 mg/Kg, respectively. Mean concentration of Cd in the industrial, agricultural and highway soils was 4.9±3.8, 1.9±1.2 and 0.95±0.4 mg/Kg, respectively, and mean concentration of Zn was 214±111.5, 112±47 and 107±39.5 mg/Kg, respectively. Maximum of Pb, Cd and Zn concentrations was 345, 8.5 and 325.5 mg/Kg, respectively that in industrial areas and highway it was significantly more than agricultural areas (p< 0.05).CONCLUSION: Results of this study showed that the soil of industrial areas and highway of Amol-Babol is relatively polluted. Therefore, more supervision on removal of all pollutants is necessary.